Estimation of interfade duration for Ku- and Ka-band satellite communication system in equatorial Malaysia - Yunus, M. M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Knowledge of the dynamics characteristics of rain fade is important for satellite communication (SatCom) system designs since it determines the system availability as well as provides essential information for the implementation of Propagation Impairment Mitigation Techniques (PIMTs). In particular, the interfade duration due to rain - appear as one of the crucial parameter to provide estimation for the system requirements to recover in time before the next outage. In fact, this is even much more critical in tropical/equatorial region and at high frequencies (Ku-band and above). In this paper, we present an estimation of interfade duration in Ku- and Ka-band by applying the Stratiform-Convective Synthetic Storm Techniques (SC-SST) and a good agreement with measured statistic has been found. The performance of the prediction model in estimating interfade duration characteristic is evaluated quantitatively by means of figure of merit, and the result show RMS error of 0.91 for prediction at Ku-band. In addition, comparison of the SC-SST in equatorial region with the measurement results in temperate area for Ka-band clearly point out significant differences among two regions and also the needs of the measurement results for further validation activities in equatorial area.